2010
DOI: 10.1093/hmg/ddq144
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association identifies ATOH7 as a major gene determining human optic disc size

Abstract: Optic nerve assessment is important for many blinding diseases, with cup-to-disc ratio (CDR) assessments commonly used in both diagnosis and progression monitoring of glaucoma patients. Optic disc, cup, rim area and CDR measurements all show substantial variation between human populations and high heritability estimates within populations. To identify loci underlying these quantitative traits, we performed a genome-wide association study in two Australian twin cohorts and identified rs3858145, P = 6.2 × 10−10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
124
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(132 citation statements)
references
References 39 publications
(45 reference statements)
7
124
1
Order By: Relevance
“…Recently, several POAG susceptibility loci were identified by genome-wide association (GWA) studies [16][17][18][19][20] and were replicated in multiple ethnicities: 7q31.2 between CAV1 and CAV2, 16,21 9p21.3 with CDKN2B-AS1, 19,20,[22][23][24][25][26] 10q21.3 with ATOH7, 17,18,22,27 and 14q23.1 between SIX1 and SIX6. 17,20,22,28 One of the GWA studies demonstrated the association of POAG with six SNPs that flanked the ZP4, PLXDC2, and TMTC2 genes located at chromosome loci 1q43, 10p12.31, and 12q21.31, respectively, in a Japanese population; 29 however, these associations were not replicated in a South Indian, 30 Afro-Caribbean, 24 or Chinese 31 population.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several POAG susceptibility loci were identified by genome-wide association (GWA) studies [16][17][18][19][20] and were replicated in multiple ethnicities: 7q31.2 between CAV1 and CAV2, 16,21 9p21.3 with CDKN2B-AS1, 19,20,[22][23][24][25][26] 10q21.3 with ATOH7, 17,18,22,27 and 14q23.1 between SIX1 and SIX6. 17,20,22,28 One of the GWA studies demonstrated the association of POAG with six SNPs that flanked the ZP4, PLXDC2, and TMTC2 genes located at chromosome loci 1q43, 10p12.31, and 12q21.31, respectively, in a Japanese population; 29 however, these associations were not replicated in a South Indian, 30 Afro-Caribbean, 24 or Chinese 31 population.…”
Section: Introductionmentioning
confidence: 99%
“…Humans and mice show marked intraspecies variations in the total number of retinal ganglion cells (RGCs) and optic disc area, which are directly correlated measures [1][2][3][4][5]. In principle, this variation may arise from differences in RGC genesis or in the extent of developmental culling.…”
Section: Introductionmentioning
confidence: 99%
“…disease in humans [15][16][17], with optic nerve aplasia being the primary phenotype in both species. Recent genome-wide association studies (GWAS) have identified the ATOH7 locus as a major determinant of variation in the optic disc area in normal human populations [3][4][5] and a contributing factor in the susceptibility to glaucoma disease [18,19]. However, a substantial cohort of RGCs are Math5-independent, and only a small fraction of Math5+ cells adopt the RGC fate [20].…”
Section: Introductionmentioning
confidence: 99%
“…Recent genome-wide analyses using normal populations have identified two genes significantly associated with IOP, GAS7 and TMCO1 (van Koolwijk et al 2012). Similar analyses for optic nerve parameters associated with glaucoma risk have identified CDKN2BAS and SIX1SIX6 as genetic risk factors contributing to cup-to-disc-ratio (Ramdas et al 2010;Fan et al 2011) and ATOH7 as an important determinant of optic nerve size (Macgregor et al 2010). Populations from around the world have been used to identify genetic factors contributing to CCT, one of the most heritable of the quantitative ocular traits (Toh et al 2005).…”
Section: Quantitative Ocular Traits That Are Risk Factors For Glaucomamentioning
confidence: 90%
“…Additionally, genetic variants associated with quantitative ocular traits that are risk factors for common forms of glaucoma have also been identified. These include IOP (van Koolwijk et al 2012), central corneal thickness (CCT) (Vithana et al 2011;Lu et al 2013), and optic nerve parameters including cup-to-disc ratio and optic nerve area (Ramdas et al 2010;Macgregor et al 2010;Axenovich et al 2011) (Table 3). The clinical features of POAG generally include both elevated IOP and optic nerve degeneration.…”
Section: Common Variants Contributing To Adult-onset Glaucoma With Comentioning
confidence: 99%